COMPARATIVE ANALYSIS OF THE RESULTS OF GENERAL TRAFFIC MEASUREMENTS FOR THE SILESIAN VOIVODESHIP AND POLAND - Elżbieta MACIOSZEK; Damian LACH (Scientific Journal of Silesian University of Technology. Series Transport)
General traffic measurements are carried out to determine basic traffic characteristics on voivodeship roads and national roads. The basic measure obtained during these measurements is annual average daily traffic. This is the number of vehicles that have passed over a specified point of a road section within a 24-h period on average within one year. For voivodeship roads, average daily traffic, average daily evening traffic and average daily night traffic are also determined. In the case of national roads, average daily summer traffic and average daily winter traffic are determined. The article presents a comparison of the characteristics for national roads in the Silesian Voivodeship and for national roads in Poland in the period 2000-2015.